Stretchable tactile sensor with high sensitivity and dynamic stability based on vertically aligned urchin-shaped nanoparticles. (August 2020) - Yu, Z.; Ying, W.B.; Pravarthana, D.; Li, Y.Y.; Mao, G.Y.; Liu, Y.W.; Hu, C.; Zhang, W.X.; He, P.X.; Zhong, Z.C.; Qu, S.X.; Zhang, R.Y.; et al.
Abstract: Stretchable tactile sensor (STS) is promising for wearable electrical devices, human-machine interfaces, and electronic skin. However, developing a STS based on piezoresistive composite high-pressure sensitivity and dynamic stability remains challenging because stretching deformation destroys the original dispersed state of conductive fillers. This interference of stretching strain on the pressure sensing greatly reduces device performance. Here, we realize an STS based on a piezoresistive composite with different elastic modulus in its functional regions. The composite contains high elastic modulus region (59.1 MPa) of vertically aligned columns of urchin-shaped nanoparticles, and low elastic modulus region (2.4 MPa) of pure matrix. The sensor exhibits high-pressure sensitivity (12.05 kPa −1 ) owing to the increased conductive contact area between urchin-shaped nanoparticles in the high elastic modulus region. While stretching to 400% strain, the sensor exhibits excellent dynamic stability via strain accommodation in the low elastic modulus region. Our design to separate sensing from multiple stimulus by elastic modulus regulation is easy operative and universal. In addition, the sensor has a low hysteresis coefficient (5.25%), a good detection limit (22 mg), a low response/recovery time (<50 ms), and an excellent mechanical durability (cycled 10, 000 times). Finally, we demonstrate the use of our STS for several important stretchable electronic applications to show the feasibility of our design. Graphical abstract: A piezoresistive composite filled with vertically aligned columns of urchin-shaped nanoparticles realizes strain accommodation at large deformation using its functional regions with different elastic moduli. Hence, a stretchable tactile sensor based on it exhibits high performance to keep pressure sensitivity greater than 10 kPa −1  at stretching strain of 400%. Image 1 Highlights: Stretchable tactile sensor is an important front-end component for many soft and wearable electronic systems. Vertically aligned urchin-shaped nanoparticles enable the sensor to be sensitive for pressure (>10 kPa −1 ) and stable under large strain (400%). It is an easy-operative and universal approach to separate the sensing property from multiple stimulus via elastic modulus regulation. The fabricated sensor has been used in wearable devices, human-machine interfaces, and electronic skin.